Distinct Bacterial Communities Associated with Massive and Branching Scleractinian Corals and Potential Linkages to Coral Susceptibility to Thermal or Cold Stress - Liang, Jiayuan; Yu, Kefu; Wang, Yinghui; Huang, Xueyong; Huang, Wen; Qin, Zhenjun; Pan, Ziliang; Yao, Qiucui; Wang, Wenhuan; Wu, Zhengchao (Frontiers in Microbiology, 2017)
It is well known that different coral species have different tolerances to thermal or cold stress, which is presumed to be related to the density of Symbiodinium. However, the intrinsic factors between stress-tolerant characteristics and coral-associated bacteria are rarely studied. In this study, 16 massive coral and 9 branching coral colonies from 6 families, 10 genera and 18 species were collected at the same time and location (Xinyi Reef) in the South China Sea to investigate the bacterial communities. The results of an alpha diversity analysis showed that bacterial diversities associated with massive corals were generally higher than those with branching corals at different taxonomic levels (phylum, class, order and so on). In addition, hierarchical clustering tree and PCoA analyses showed that coral species were clustered into two large groups according to the similarity of bacterial communities. Group I consisted of massive Goniastrea, Plesiastrea, Leptastrea, Platygyra, Echinopora, Porites and Leptoria, and group II consisted of branching Acropora and Pocillopora. These findings suggested that both massive corals and branching corals have their own preference for the choice of associated bacteria, which may be involved in observed differences in thermal/cold tolerances. Further analysis found that 55 bacterial phyla, including 43 formally described phyla and 12 candidate phyla, were detected in these coral species. Among them, 52 phyla were recovered from the massive coral group, and 46 phyla were recovered from the branching coral group. Formally described coral pathogens have not been detected in these coral species, suggesting that they are less likely to be threatened by disease in this geographic area. This study highlights a clear relationship between the high complexity of bacterial community associated with coral, skeletal morphology of coral and tolerances to thermal or cold stress.